Cytome micronucleus assays with a metabolically competent human derived liver cell line (Huh6): A promising approach for routine testing of chemicals?. (8th November 2018) - Mišík, Miroslav; Nersesyan, Armen; Bolognesi, Claudia; Kundi, Michael; Ferk, Franziska; Knasmueller, Siegfried
Abstract : One of the main problems of in vitro genotoxicity tests is the inadequate representation of drug metabolizing enzymes in most indicator cell lines which are currently used. We identified recently a human derived liver cell line (Huh6) which detected induction of DNA damage by representatives of different groups of promutagens without enzyme mix and showed that these cells are more suitable in terms of reproducibility and sensitivity as other currently used liver derived lines. We developed a protocol for micronucleus (MN) cytome assays with these cells and validated the procedure in experiments with representatives of different groups of directly and indirectly acting genotoxic carcinogens (MMS, cisplatin, PhIP, IQ, NDMA, B(a)P, AFB1, etoposide, and H2 O2 ). The optimal cytochalasin B concentration in combination with 48 hr treatment was found to be 1.5 μg/mL and leads to a cytokinesis block proliferation index in the range between 1.7 and 2.0. The morphological characteristics of different nuclear anomalies which reflect DNA damage (MN, nuclear bridges, and buds) and their baseline frequencies in untreated cells were characterized, and the rates which are required to cause significant effects were calculated. All compounds caused dose dependent induction of MN when the cells were treated for 24 hr, longer and shorter exposure times were less effective. Experiments with different serum levels (fetal bovine serum [FBS]) showed that 10% FBS in the medium (instead of 4%) causes a substantial increase of the sensitivity of the cells. Our results indicate that the new protocol is a promising approach for routine testing of chemicals. Environ. Mol. Mutagen. 60: 134–144, 2019. © 2018 The Authors. Environmental and Molecular Mutagenesis published by Wiley Periodicals, Inc. on behalf of Environmental Mutagen Society.